Analysis of the thermal mapping of thermolabile drugs in waterway transport in the State of Para (Research, Society and Development, 2021)
Objective: To analyze the thermal mapping of thermolabile drugs (MT) by waterway modal in the State of Para. Methods: This is a quantitative study, of data obtained through the transport of MT in the year 2020. Data collections were obtained through the records made by measuring the temperature and humidity of the thermal containers during the 12 hours of transportation to their destination. Results: The results showed thermal differences in the containers used. The Thermal Container 1 (export model EPS styrofoam with special double wall) the variation was minimal and did not compromise the transported drugs. The minimum temperature was 2.2ºC and maximum 7ºC. The humidity also reached minimum (65%) and maximum (71%) values. The Thermal Container 2 (EPS common polystyrene) represented a significant increase in the original temperature and humidity. The parameters reached were 17.4ºC and 89%. Conclusion: The discrepancy between containers 1 and 2, indicates that it is not the means of transport (waterway modal) that influence the thermal stability of pharmaceutical products, but rather, the non-correct packaging, in specific containers of medicines. In this sense, the presence of the pharmaceutical professional becomes necessary in this segment.